Dispositivo de extração de cálculos intracoledocianos por inclusão em polímero auto expansível - Nascimento Neto, Saturnino Ribeiro do (2017)
General surgery has experienced after the nineties, with the development of laparoscopy, spectacular improvement in outcomes. Lower morbidity and mortality is due to less surgical trauma caused by surgeries performed by small orifices. The technological development of rigid and flexible endoscopes gave doctors direct access to abdominal pathologies without the need for large openings in the coelomic cavity. Thus, there was a great improvement not only in the aesthetic results, but mainly in the reduction of morbidity. In biliary surgeries this was not different. With the improvement of the laparoscopic surgical technique, the endoscopic cirurgical approach was favored. However, the reality of laparoscopy in many places is not present in the treatment of choledocholithiasis, especially when such pathology is treated in centers with lower financial resources. Removal of stones from the main biliary tract requires the use of high-cost fibroscopes as well as high-value disposable devices, forcing the surgeon devoid of such resources, many times undergoing conventional surgery or at a minimum, increasing the difficulty of the procedure by laparoscopic approach. With the purpose of equating this difficulty, it is proposed with this device, another concept of approach to this problem, novel, tested in macro environment, with the use of balloon catheter containing self expanding polymer capable of grasping the calculi of the common bile duct by inclusion. Using the trans-operative cholangiography precepts, the new method proposes to extract the principal biliary tract calculi indirectly with the help of imaging methods common to the most hospitals.